New species records of Suwallia Ricker, 1943 (Plecoptera: Chloroperlidae) from China, with description of the nymph of S. decolorata Zhiltzova & Levanidova, 1978 - Li, Weihai; Murányi, Dávid; Shi, Li (Zootaxa, 2015)
Two species of the chloroperlid genus Suwallia, S. decolorata Zhiltzova & Levanidova, 1978 and S. talalajensis Zhiltzova, 1976 are reported for the first time from the Inner Mongolia Autonomous Region of China. The habitus and diagnostic features of these two species including aedeagal structures are illustrated with color images. Additional descriptions and taxonomic notes are provided. The nymph of S. decolorata is described.